Sustainability and Service Quality of Manado Beach Walk Tourism Objects in Supporting Manado City Tourism Industry - Kondoj, Telly Hetty Isje; Solang, Jeanlly A.; Gumolili, Youdi Y.; Sendow, Deby Ch.; Takaendengan, Mita E. (Pusat Studi Pembangunan dan Pemberdayaan, 2024)
Malalayang Beach Walk area is one of the tourist attractions in Manado City. Formerly this location was a place to sell a variety of culinary, but it has not been well arranged. Then this location was developed and made into a tourist attraction. The research method used is a qualitative method obtained by data collection techniques such as interviews, observation, and documentation. Based on the results of research, there is a strength that is the view of the beach, has attractions such as sports venues, children's playgrounds. Weaknesses are the lack of security levels in children's playgrounds, the absence of terraces in places to eat outside so that visitors feel less comfortable, lack of cleanliness levels of toilets, some facilities that are not maintained such as trash cans. The opportunity is that the Malalayang area is managed by the Manado city government.